AKIBAT HUKUM BAGI KONSORSIUM YANG DIPUTUS BERSALAH DALAM PERKARA KOMISI PENGAWAS PERSAINGAN USAHA (KPPU) - Pradhana, Wisnu Aji; Pujiyono, ' (Jurnal Privat Law, 2020)
AbstractThe purpose of this article is to examine and analyze legal consequences for the Consortium who were found guilty in the case of the KPPU’s decision. This research is a normative or doctrinal with prescriptive and applied properties. The writing uses secondary data as the type of data. The legal material collection technique of this research is by studying documents or library studies conducted by collecting legal materials both primary and secondary, then read, studied and analyzed to answer legal problems as a support for this research. The KPPU’s decision to make the Consortium as one of the reported entities resulted in legal consequences for the consortium. Legal consequences in unfair competition and prohibition of monopoly in Indonesia are not only administrative sanctions and civil sanctions, but there are also criminal sanctions in the form of fines and imprisonment as a substitute for fines.Keywords: Legal Consequences; Konsorsiu; KPPU; Legal SubjectsAbstrakArtikel ini bertujuan untuk menganalisa Akibat Hukum Bagi Konsorsium yang di Putus Bersalah dalam perkara Komisi Pengawas Persaingan Usaha (KPPU). Penelitian ini merupakan penelitian normatif atau doktrinal dengan sifat preskriptif dan terapan. Jenis data atau bahan hukum yang digunakan adalah data sekunder. Teknik pengumpulan bahan hukum yang digunakan adalah dengan studi dokumen atau studi kepustakaan yang dilakukan dengan cara mengumpulkan bahan hukum. Putusan KPPU yang menjadikan Konsorsium sebagai satu entitas terlapor mengakibatkan akibat hukum bagi konsorsium. Akibat Hukum dalam persaingan udaha tidak sehat dan larangan monopoli di Indonesia tidak hanya sanksi administratif dan sanksi perdata, akan tetapi terdapat pula sanksi pidana berupa denda dan pidana kurungan penganti denda.Kata Kunci: Akibat Hukum;Konsorsium; KPPU; Subyek Hukum